Study of Misapplication on the Law by the Notary Regional Supervisory Council in Imposing Sanctions on Notaries Who Make Deeds - IRIANTORO, Agung; SHAFIRA, Chica Nur (Journal of Political And Legal Sovereignty, 2024)
Purpose:The result is that the MPWN decision must be appealed to someone other than the Central Supervisory Board. Because there is a rule in Article 28 paragraph (2) of PERMENKUMHAM number 15 of 2020, namely MPW has the authority to reject objections to decisions on oral warning sanctions and written warnings, in this case, the oral warning sanctions and written warnings are final and cannot be appealed.Methodology:This research is a descriptive analysis. Namely, the discussion is done by presenting and explaining data thoroughly, in detail and systematically. This type of research is normative legal research, a legal research method that examines library materials.Findings:The result is that the MPWN decision must be appealed to someone other than the Central Supervisory Board. Because there is a rule in Article 28 paragraph (2) of PERMENKUMHAM number 15 of 2020, namely MPW has the authority to reject objections to decisions on oral warning sanctions and written warnings, in this case, the oral warning sanctions and written warnings are final and cannot be appealed.Implication:However, with the law on judicial power and the law on administrative court, the party who objected can file a legal remedy in Administrative Justice. The MPWN decision can be subject to State Administration, and the proper application of the law is outlined in Article 17, paragraph (2) of the amendment law. As a supervisor, the MPWN must remain objective and thorough to prevent errors in the application of the law from recurring.